Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ehf2.13106
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of high‐intensity interval training in patients with left ventricular assist devices: a pilot study

Abstract: Aims Patients with left ventricular assist device (LVAD) suffer from persistent exercise limitation despite improvement of their heart failure syndrome. Exercise training (ET) programmes to improve aerobic capacity have shown modest efficacy. High‐intensity interval training (HIIT), as an alternative to moderate continuous training, has not been systematically tested in this population. We examine the feasibility of a short, personalized HIIT programme in patients with LVAD and describe its effects on aerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Counteracting the natural decline of VO 2peak with age by adequate physical activity positively modifies the cardiovascular risk profile 30 . Although most exercise studies with LVAD patients prescribed aerobic activities and demonstrated patient safety, 31 short‐term improvement of VO 2peak by applying more intense exercise has also been demonstrated 32,33 . However, it may be argued that especially LVAD/EOV+ may be put at risk for pulmonary congestion in case of more intense and longer bouts of exercise, such as the “Norwegian model” with a 4x4min interval up to 90% of maximal heart rate 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Counteracting the natural decline of VO 2peak with age by adequate physical activity positively modifies the cardiovascular risk profile 30 . Although most exercise studies with LVAD patients prescribed aerobic activities and demonstrated patient safety, 31 short‐term improvement of VO 2peak by applying more intense exercise has also been demonstrated 32,33 . However, it may be argued that especially LVAD/EOV+ may be put at risk for pulmonary congestion in case of more intense and longer bouts of exercise, such as the “Norwegian model” with a 4x4min interval up to 90% of maximal heart rate 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…68 Exercise training in this population has shown to be beneficial for both improvements in exercise capacity and patient-reported health outcomes (Table 4). [68][69][70][71][72][73][74][75] However, despite this, and despite the fact that the Centers for Medicare & Medicaid Services now covers CR in patients on LVAD support under HF, only 42% of eligible patients in this population utilize CR. 76…”
Section: Exercise Prescription and Trainingmentioning
confidence: 99%
“…35 In this population, HIIT has shown promise with some preliminary data. 73,84 However, more research is needed on the safety of HIIT in this population and should only be considered in select patients, based upon factors such as age, balance, and overall functional abilities.…”
Section: Exercise Prescription and Trainingmentioning
confidence: 99%
“…Hence, a recent, admittedly small retrospective study of 28 discharged COVID-19 survivors reported that rehabilitation triggered by HIIT, with endurance training at the maximum tolerated exercise load was both safe and feasible (49). To this end HIIT has successfully been implemented as a rehabilitation strategy in other "high risk" populations, as demonstrated in larger studies on patients at risk or with prevalent ischaemic heart disease, heart failure, chronic obstructive pulmonary disease, cystic fibrosis, and asthma with effects on parameters such as cardiorespiratory fitness (VO 2 peak) and exercise capacity with few reports of severe adverse events, even in patients with left ventricular assist devices (36,41,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). The rate of cardiovascular complications has been reported of 1 per 23,182 h of high-intensity exercise (51) and later studies have confirmed that HIIT is safe in patients with cardiovascular disease (53).…”
Section: Hiit: Is It Effective And/or Safe In Covid-19?mentioning
confidence: 99%